DIGNIFIED DEATH IN BRAZIL - Reckziegel, Janaína; Coninck, Beatriz Diana Bauermann (Unoesc International Legal Seminar, 2017)
The present article seeks to argue about the history of death, the philosophical opinions on this phenomenon; to check whether euthanasia and assisted suicide would be probable motivators for the happening of the called slippery slope; whether orthothanasia would be a dignified way to die; to evaluate the concrete validity of the constitutional right to dignified death in the Brazilian juridical legislation and to examine the palliative care methods applied in this country, by using the deductive method of qualitative approach with bibliographic research technique on national e international references. It is concluded that may be found the traditional, the modern and the contemporary as ways of dying in Brazil.